Report of the Commutes for Training in Evaluation - Planning Commission (Planning Commission, 1979)
In pursuance of the recommendations of the Conference of the Heads of State Evaluation Organisations held in New Delhi-in November, 1977, the Government of India vide their 0.M.No.PE0/10-8/77-TE, dated June 23, 1976 set up a Committee for-draining in Evaluation under the chairmanship of Secretary, Planning Commission (Appendix I). Although the Committee was initially constituted for a period of. six months, its tenure had. to be extended until September 30, 1979 in view of the organisation of three experimental Regional Workshops for the Senior level evaluation personnel and preparing the syllabus for the Supervisory level personnel by a sub-committee.
Programme Evaluation Organisation Planning Commission Government of India New Delhi